The Impact Of Covid-19 In Education Field And Teachers As Agents Of Change - Martina Napratilora; Mardiah mardiah; Windra Arjuni; Khoirin Khoirin (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
Covid-19 caused many changes to the education field and the teachers. In normal situations and conditions, the teaching and learning process is done face-to-face in class, but it is very different now. The teachers and the students have to do online learning using learning applications. These changes cause the stakeholders to face much impact, especially in the process of transferring knowledge. This research aimed to describe the impact of Covid-19 in the education field and teachers as agents of change. This research used a literature study to find out related theories to the research problems. The research sources are journals, books, documentation, the internet, the library, and so on. The results show that Face to face learning has to move to daring learning at home using technology internet. The teachers have to learn more about how to use daring media as a tool in the teaching and learning process like how to apply Google Classroom, Facebook, Twitter, Zoom, and YouTube. The teachers also have to improve their capability in online teaching and learning processes by following workshops, coaching, seminar, and KKG. Not only the teacher but also the students will do the same thing as the teacher learns how to do daring learning at home.